ACTS ISSUED BY THE PRESIDENT OF THE RUSSIAN FEDERATION AND FOREIGN POLITICAL LEADERS: LEGAL ANALYSIS - Loshkarev, Igor; Tchinaryan, Elena; Lutovinova, Natalya (Revista Inclusiones, 2020)
The article considers the legal status of acts issued by the President of the Russian Federation and foreign political leaders. The article aims at determining the practical significance of the right enjoyed by heads of state to issue their own acts, as well as recognizing the essence, role, effectiveness and further development of such a right in the Russian Federation and foreign countries. This scientific study was conducted in several stages. For a start, the authors selected a research topic and justified its relevance. Then they determined the objective and tasks of the study and analyzed the corresponding scientific literature. The authors selected proper research methods, including general and special scientific methods. General scientific methods included the methods of system analysis, induction and deduction. Specific scientific methods of cognition comprised analytical, formal-legal, historical-legal and system-structural methods. After obtaining information on the issue under study, the authors processed and analyzed it.